The Effect of Financial Performance Indicators on Stock Prices in the Banking Sector Listed on the IDX - Ristanti, Nadia; Pratiwi, Dian Mega (Indonesian Journal Publisher, 2025)
The stability of the banking sector is a crucial foundation for the resilience of the national financial system, especially in the face of global economic dynamics. This study aims to analyze the effect of Earnings Per Share (EPS), Price to Book Value (PBV), and Market Capitalization (MC) on the stock prices of banks listed on the Indonesia Stock Exchange (IDX). A quantitative approach is employed using multiple linear regression analysis, based on secondary data from financial statements and monthly stock prices of three selected banks during the period from January 2022 to December 2023. The results show that all three independent variables have a significant effect on stock prices, both simultaneously and partially. EPS and PBV have a negative influence, while MC has a positive influence. These findings indicate that while fundamental financial performance is important, market perception of a company’s value and size also plays a critical role in determining stock prices. This study recommends that investors consider key financial indicators in their investment decisions and encourages bank management to maintain balanced financial performance. Future research is suggested to include macroeconomic variables such as interest rates, inflation, or monetary policy to provide a more comprehensive analysis of stock price movements in the banking sector.